Deliberating the Dialogues: a critical examination of the nature and purpose of a Daily Dispatch public journalism project - Amner, Roderick John (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2010)
This thesis critically examines the nature and purpose of a series of four town-hall-like meetings, the Community Dialogues, held in the townships and suburbs of East London, South Africa, in 2009. They were undertaken by a mainstream, commercial newspaper, the Daily Dispatch, under the banner of the worldwide public journalism movement. Following Christians et al (2009), the thesis sets out a normative framework of media performance in a democracy, including a detailed and critical normative theory of the 'facilitative role' proposed and developed by Haas (2007), one of the public journalism movement's key advocate-theorists. It also draws on a variety of theoretical frameworks and perspectives in the fields of Political Studies and Media Studies to provide an analytical overview of the complex matrix of political and media contexts "“ at the macro (global), meso (national) and micro (local) levels "“ that have helped give impetus to the Community Dialogues and also shaped their ongoing operation as a public journalism strategy in the South African context. Following a critical realist case study design, the thesis goes on to provide a narrative account of the Dialogues based on in-depth interviews exploring the motivations, self-understandings and perceptions of those journalists who originated, directed and participated in this project, as well as observation of a Community Dialogue, and an examination of some of the journalistic texts related to the Dialogues. This primary data is then critically evaluated against normative theories of press performance, especially Haas's 'public philosophy' of public journalism. The thesis found that apart from their undoubted success in generating a more comprehensive and representative news agenda for the newspaper, the Dialogues often fell short of Habermas's (1989) proceduralist-discursive notion of the 'deliberating public', which sees citizens share a commitment to engage in common deliberation and public problem solving. This can be attributed to a number of problems, including some important theoretical/conceptual weaknesses in the Community Dialogues' project design, the relative immaturity of the project, the domination of civil society by political society in the South African political context, and a number of organisational constraints at the Daily Dispatch. On the other hand, the newspaper's editorial leadership has shown clear commitment to the idea of expanding the project in the future, establishing a more a more structured programme of community engagement, and nurturing a more sustainable public sphere, including the building of a more dialectical relationship between the Dialogues and civil society.
Keywords: Daily Dispatch (East London, South Africa); Journalism -- South Africa -- East London; Citizen journalism -- South Africa -- East London